Regulation of Oxygen in the Tumor Microenvironment Synergizes with Immunotherapy to Suppress Tumor Progression - Shoucheng Wang; Yongjie Chi; Danyang Wang; Kai Zhao; Lianyan Wang (Journal of Functional Biomaterials)
Hypoxia represents a crucial characteristic of the tumor microenvironment, which is closely related to cell proliferation, angiogenesis, and metabolic responses. These factors will further promote tumor progression, increase tumor invasion, and enhance tumor metastasis potential. A hypoxic microenvironment will also inhibit the activity of infiltrated immune cells in the tumor microenvironment, leading to the failure of cancer immunotherapy. Additionally, the hypoxic tumor microenvironment contributes to resistance to conventional therapies and leads to unfavorable prognoses. This review discusses advancements in strategies aimed at ameliorating tumor hypoxia within the microenvironment and modulating immune cell responses against tumors.